Furan Oxidation Reactions in the Total Synthesis of Natural Products - Makarov, Anton S.; Uchuskin, Maxim G.; Trushkov, Igor V. (Synthesis, 2018)
Recent developments on the transformations of furans under oxidative conditions toward the total synthesis of complex natural compounds are discussed. Reactions and methods are classified according to the type of oxidant used. Comparisons are then made between all the strategies to provide a comprehensive overview. This review covers the most prominent work published from 2011 until 2017.1 Introduction2 Reagents and Methods for Oxidation of the Furan Ring2.1 Singlet Oxygen2.2 Peroxides and Hydroperoxides2.3 Quinones2.4 Halogen-Based Oxidants2.5 Chromium-Based Oxidants3 The Achmatowicz Reaction3.1 Halogen-Based Oxidants3.2 Hydroperoxides3.3 Enzymatic Oxidation4 Conclusion
Keywords: furans; oxidation; rearrangement; natural products; total synthesis